THE MODERN STATUS OF THE VELIKAYA RIVER DELTA ON THE STATE OF PRIMARY PRODUCERS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Primary producers are an integral part of freshwater ecosystems. Phytoplankton forms the basis of the trophic pyramid, participates in the formation of water quality and acts as a sensitive indicator of the state of the reservoir. The ability of macrophytes to accumulate mineral and organic substances makes them active participants in the self-purification of natural waters. Higher aquatic plants are characterized by conservatism to short-term changes in the environment, but changes in vegetation over the years may indicate anthropogenic transformation of ecosystems. The contribution to maintaining the stability of the functioning and biodiversity of the ecosystem makes phytoplankton and macrophytes compulsory research objects aimed at studying the state of water bodies. The aim of the work was the study of primary producers as bioindicators of the ecological status of the Velikaya river delta in the summer of 2018. As a result, 127 phytoplankton taxa from 8 phylums were found: Chlorophyta, Bacillariophyta, Cyanobacteria, Euglenophyta, Chrysophyta, Dinophyta, Cryptophyta, Charophyta. The species richness was dominated by the Chlorophyta (42.5%), Bacillariophyta (25.2%), Cyanobacteria (11.1%). According to the ecological and geographical analysis of the delta algaflora, cosmopolitan, freshwater, planktonic forms of microalgae dominate, preferring neutral and weakly alkaline waters. Water quality assessment revealed the beta-mesosaprobic nature of the waters, which indicates moderate pollution of the water area. In the composition of macrophytes, 43 species from 3 phylums were identified: Magnoliophyta, Equisetophyta, Chlorophyta. By species composition, angiosperms dominated (95.3%), of which 46.3% were dicotyledons and 53.7% - monocotyledons. Hygrophytes (34.9%) and hydrophytes (32.6%) prevailed in terms of ecological structure. The leading role in the overgrowing of the delta belonged to high-grass helophytes and rooting hydrophytes with leaves floating on the water. A total of 37 saprobiont flora were found. The total index of saprobity was 277 points.